Virulence and Replicative Fitness of HIV-1 Transmitted/Founder (T/F) Viruses Harbouring Drug Resistance-Associated Mutation - Aanand Sonawane; Deepak Selvam; Ling Yue; Manohar Nesakumar; Sandhya Vivekanandan; Manickam Ashokkumar; Eric Hunter; Luke Elizabeth Hanna (Viruses)
The biological characteristics of early transmitted/founder (T/F) variants are crucial factors for viral transmission and constitute key determinants for the development of better therapeutics and vaccine strategies. The present study aimed to generate T/F viruses and to characterize their biological properties. For this purpose, we constructed 18 full-length infectious molecular clones (IMCs) of HIV from recently infected infants. All the clones were characterized genotypically through whole genome sequencing and phenotypically for infectivity, replication kinetics, co-receptor usage, as well as their susceptibility to neutralizing antibodies and entry inhibitors using standard virological assays. Genotypic analysis revealed that all the T/F clones were of non-recombinant subtype C, but some of them harboured the Y181C drug resistance mutation associated with resistance to the non-nucleoside reverse transcriptase inhibitor (NNRTI) class of antiretroviral drugs. In vitro studies showed that while all the IMCs were capable of replicating in PBMCs and utilized the CCR5 co-receptor for cellular entry, the drug-resistant variants had significantly lower replicative capacity and per particle infectivity than the drug-sensitive viruses. Both exhibited similar sensitivities to a standard panel of broadly neutralizing monoclonal antibodies and viral entry inhibitors. These findings suggest that despite their diminished replicative fitness, the drug-resistant T/F variants retain transmission fitness and remain susceptible to neutralizing antibody-based interventions and viral entry inhibitors.